A Culture-Adapted Strain of Babesia bovis Has Reduced Subpopulation Complexity and Is Unable to Complete Its Natural Life Cycle in Ticks - Alzan, Heba F.; Bastos, Reginaldo G.; Laughery, Jacob M.; Scoles, Glen A.; Ueti, Massaro W.; Johnson, Wendell C.; Suarez, Carlos E. (Frontiers in Cellular and Infection Microbiology, 2022)
Babesia bovis natural field strains are composed of several geno-phenotypically distinct subpopulations. This feature, together with possible epigenetic modifications, may facilitate adaptation to variable environmental conditions. In this study we compare geno-phenotypical features among long-term (more than 12 years) (LTCP) and short-term cultured B. bovis parasites (STCP) derived from the B. bovis S74-T3Bo strain. LTCPs intraerythrocytic forms are smaller in size than STCPs and have faster in vitro growth rate. In contrast to its parental strain, the LTCP lack expression of the sexual stage specific 6cysA and 6cysB proteins and are unable to develop sexual forms upon in vitro sexual stage induction. Consistently, in contrast to its parental strain, LTCPs have reduced virulence and are not transmissible to cattle by vector competent Rhipicephalus microplus (R. microplus). Similar to previous comparisons among attenuated and virulent B. bovis strains, the LTCP line has decreased genomic diversity compared to the STCP line. Thus, LTCP may contribute to our understanding of adaptive mechanisms used by the parasites in response to environmental changes, protective immunity, virulence, and transmission by ticks. In addition, LTCPs may be considered as candidates for a non-tick transmissible vaccine against bovine babesiosis.